1994
DOI: 10.1109/55.320979
|View full text |Cite
|
Sign up to set email alerts
|

A simple edge termination for silicon carbide devices with nearly ideal breakdown voltage

Abstract: In this paper, a simple edge termination is described which can achieve near ideal parallel plane breakdown for silicon carbide devices. This novel edge termination involves self aligned implantation of a neutral species on the edges of devices to form an amorphous layer. With thii termination formed using argon implantation, the breakdown voltage of Schottky barrier diodes was measured to be very close to ideal plane parallel breakdown voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 6 publications
0
19
0
2
Order By: Relevance
“…The relationship under thermionic emission theory is given by [21] where is the ideality factor incorporating the tunneling currents in a practical diode. If the applied voltage is much larger than , then the exponential term in the above equation dominates, and can be approximated as (4) and can thus be determined from the experimentally obtained forward density-voltage ( ) characteristics at a given temperature.…”
Section: B I-v Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship under thermionic emission theory is given by [21] where is the ideality factor incorporating the tunneling currents in a practical diode. If the applied voltage is much larger than , then the exponential term in the above equation dominates, and can be approximated as (4) and can thus be determined from the experimentally obtained forward density-voltage ( ) characteristics at a given temperature.…”
Section: B I-v Characteristicsmentioning
confidence: 99%
“…Several techniques have been shown to reduce the field crowding at the edges, thus resulting in higher breakdown voltages. These include 1) the use of floating metal field rings (FMR) and resistive Schottky barrier field plates (RESP) as reported by Bhatnagar et al [3]; 2) the use of implantation of neutral species at the periphery of the diode to form an amorphous area around the periphery of the device [4]- [7]; and 3) the p-n junction guard-ring termination formed by a local oxide process (LOCOS) [8]. In most of these structures, the SiC surface is unpassivated and there is no dielectric isolation between devices on the chip.…”
mentioning
confidence: 99%
“…This simple structure suffers from a low blocking voltage, relative to the theoretical breakdown voltage, due to the E-Field crowding at the edge of Schottky metal contact. To relieve E-Field enhancement at the edge of diode metal contact, methods using field plates [5], mesa structures [6], Junction Termination Extension (JTE) [7], guard rings [8], and highly resistive surface regions formed by argon implants [9] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…6 The Ar + implantation into high voltage Schottky diodes has been used as edge termination. 7 The edge termination reduces the electric field crowding at the periphery of the device and thereby prevents premature voltage breakdown. It was found that at small bias voltages, the leakage current of terminated devices was higher than that of unterminated Schottky diodes.…”
Section: Introductionmentioning
confidence: 99%